Study of potential environmental factors predisposing ewes to subclinical mastitis in Greece. (February 2019) - Vasileiou, N.G.C.; Giannakopoulos, A.; Cripps, P.J.; Ioannidi, K.S.; Chatzopoulos, D.C.; Gougoulis, D.A.; Billinis, C.; Mavrogianni, V.S.; Petinaki, E.; Fthenakis, G.C.
Highlights: Prevalence of subclinical mastitis in 111 sheep flocks in Greece was 0.260. Main aetiological agents were staphylococci: 0.699 of all isolates. Min. temperature of coldest month and mean temperature 30 days before sampling were associated with subclinical mastitis. Abstract: Objectives of the work presented herewith were to investigate association of prevalence of subclinical mastitis with environmental (climatic and topographic) factors and to identify factors potentially predisposing ewes to the disease. Milk samples were collected from 2198 sheep in 111 farms, in all 13 administrative regions of Greece, for bacteriological and cytological examination. Data on farm location were collected in the field using hand-held Global Positioning System Garmin units. The geo-references were resolved to specific farm level. Prevalence of subclinical mastitis was 0.260. Main aetiological agents were staphylococci ( Staphylococcus aureus and coagulase-negative species), which accounted for 0.699 of all isolates recovered. In a multivariable mixed-effects analysis, the two environmental variables found to be associated with increased prevalence of subclinical mastitis were the minimum temperature of coldest month (coefficient: -0.084 ± 0.033, P  =  0.014) and the mean temperature for 30 days prior to sampling date (coefficient: 0.031±0.014, P  =  0.029).